PELATIHAN DAN PEMANFAATAN MULTIMEDIA MENGGUNAKAN CANVAS BAGI GURU-GURU MI MUHAMMADIYAH TANGUNAN - Hamzah Setiawan; Nur Maslikhatun Nisak; Hindarto hindarto; Mochammad Septa Sandy (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Madrasah Ibtidaiyah (MI) Muhammadiyah Tangunan Mojokerto is an elementary school located in the Tangunan Mojokerto area, East Java, which is located on Jl. Raya Tangunan No. 10 Kec. Puri Kab. Mojokerto, East Java. The MI location with the campus of the Faculty of Science and Technology, Muhammadiyah University of Sidoarjo, is about 36 KM away and can be reached within 90 minutes of travel. The development of MI Muhammadiyah Tangunan is currently still an underdeveloped school. This year, the number of students in Madrasahs is in the moderate category, namely 100 students divided into 6 batches, namely grades 1 to 6, with an average of 15 students per class. The results of the meeting held by the abdimas team with the MI school principal, it can be concluded that there are still teachers and business personnel who still do not utilize information technology, especially the canvas application. Given the existing problems, the purpose of this community service activity is media canvas training which will be followed by teachers and employees. For this reason, this activity is divided into several stages, namely observation, discussion, documentation, skills training and evaluation, as well as follow-up to MI Muhammadiyah Tangunan teachers. The target that will be planned is that teachers can understand how to apply Canvas.